2022
DOI: 10.1111/odi.14287
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic antioxidants activity in gingival crevicular fluid and saliva in advanced periodontitis

Abstract: AimEnzymatic antioxidants are the primary line of defense against oxidative and nitrosative stress. However, their involvement in the progression of periodontitis is still not well understood. The study aimed to determine the activity of enzymatic antioxidants in the gingival crevicular fluid (GCF) and saliva of patients with periodontitis.Materials and methodsThe study group of 56 patients with periodontitis (stage III and IV) and 28 healthy controls were involved. The modified plaque index, probing depth, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
(114 reference statements)
1
7
0
2
Order By: Relevance
“…The study material was whole unstimulated saliva collected from children via the spitting method. 21,26 Saliva was obtained between 7 and 9 a.m., one day after admission to the Department of Pediatrics and Nephrology at the Children's Hospital of the Medical University of Bialystok, or during a routine dental visit. Samples were taken in a separate, childfriendly room to ensure maximum patient comfort.…”
Section: Sialochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The study material was whole unstimulated saliva collected from children via the spitting method. 21,26 Saliva was obtained between 7 and 9 a.m., one day after admission to the Department of Pediatrics and Nephrology at the Children's Hospital of the Medical University of Bialystok, or during a routine dental visit. Samples were taken in a separate, childfriendly room to ensure maximum patient comfort.…”
Section: Sialochemistrymentioning
confidence: 99%
“…The collection time for saliva samples was 10 min. The time that had passed since their last meal, tooth brushing and medication intake was at least 8 h. 21,26 Immediately after sample collection, the volume of saliva was measured using a calibrated pipette with the accuracy of 100 µL. Next, salivary flow rate (SFR) was calculated by dividing the volume of the sample by the time necessary to collect it (mL/min).…”
Section: Sialochemistrymentioning
confidence: 99%
“…Estaí n�luenciada por la respuesta in�lamatoria del hueśped, contenidos en el lıquido crevicular gingival y la saliva. Además, puede ser afectada por factores ambientales y de comportamiento y su desarrollo puede ser modi�icado por factores locales (por ejemplo, el tabaquismo), condiciones adquiridas (enfermedades sisteḿicas) y factores geneticos (6) (38). Al conjunto de microorganismos presentes en la cavidad oral, se le denomina microbioma oral o bio�ilm oral.…”
Section: Impacto Del Estrés Oxidativo En La Saliva E Implicancia En L...unclassified
“…Además, existe un creciente intereś en el estudio del rol que cumplen las especies reactivas en los mecanismos etiopatogeńicos de algunas enfermedades orales. En ese sentido, la periodontitis es precisamente una enfermedad ıńtimamente relacionada con un desequilibrio de la homeostasis redox, donde la inducción de disbiosis oral y el estado in�lamatorio que se establece, colaboran en la formación de más especies oxidantes y radicales libres que dañan componentes celulares (5) (6) . En ese tipo de patologıás, una saliva con baja capacidad antioxidante no solo di�iculta el restablecimiento del estado redox salival, sino que además actúa de forma sineŕgica al estado proin�lamatorio subyacente provocando un mayor daño a nivel tisular y dentario (7) .…”
Section: Introductionunclassified
“…Salivary glutathione peroxidase, which is a marker of neutrophil antioxidant capacity, also significantly higher in periodontitis. 27 Growth Factors in Periodontitis: Growth factors play a variety of roles in immune responses, and elevated levels of TGF-, epidermal growth factor, and vascular endothelial growth factor have been found in periodontitis patients. However, only a few studies have found a link between salivary hepatocyte growth factor and periodontitis.…”
Section: Diagnosis Of Periodontitis Using Salivary Biomarkersmentioning
confidence: 99%